A 96-well-plate–based method for the estimation of alpha-amylase activity using miniaturises 3,5-DINITROSALICYLIC ACID (DNSA) colorimetric method - Noor Syaffinaz Noor Mohamad Zin,; Nur Ain Sabrina Azmi,; Nursarah Syamimi Anuar,; Syahirah Ain Shafie,; Muhamammad Aiman Faris Maznan,; Yong, Meng Goh; Nurdiana Samsulrizal, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The DNSA assay has been widely employed for the in vitro detection and quantification of alpha-amylase inhibitory activity. However, the conventional method is associated with inconsistencies between protocols and requires a large volume of samples and other assay reagents that can compromise accurate quantitation. Therefore, the study aimed to develop a reliable, simple, and rapid analytical method for determining α-amylase activity. The developed method was carried out in 96-well microplates with a total volume of 250 μL and a total assay time of 1 hr, including pre-incubation. The method was validated for linearity, the limit of detection (LOD), the limit of quantitation (LOQ), and precision. A higher coefficient of determination (R2) value was observed for the developed method as compared to the conventional method (0.9983 ± 0.0003 vs 0.9667 ± 0.0383). The coefficient of variation (CV%) of each data point was less than 15%, indicating excellent data precision. The optimum assay conditions were identified at 2 U/mL of enzyme solution and 5% (w/v) starch solution at 50 °C incubation temperature with an IC50 value of 0.026 ± 0.005 mg/mL. It is concluded that the developed method is practical, precise, and accurate for estimating α-amylase inhibitory activity and would provide reproducible results.